High Performance of Normally‐On and Normally‐Off Devices with Highly Boron‐Doped Source and Drain on H‐Terminated Polycrystalline Diamond. (25th January 2023) - Zhu, Xiaohua; Shao, Siwu; Chan, Siyi; Tu, Juping; Ota, Kosuke; Huang, Yabo; An, Kang; Chen, Liangxian; Wei, Junjun; Liu, Jinlong; Li, Chengming; Kawarada, Hiroshi
Abstract: Diamond exhibits large application potential in the field of power electronics, owing to its excellent and desirable electronic properties. However, the main obstacles to its development originate from the small‐sized single‐crystal wafers and the instability of the electrical conductivity. This work presents a metal‐oxide‐semiconductor field‐effect transistor (MOSFET) on a diamond substrate derived from a five‐inch (110) highly preferred polycrystalline diamond film. The MOSFETs with excellent performance are fabricated by combining an H‐terminated channel and an epitaxially grown boron‐doped layer as the source/drain contacts of the diamond devices. According to the electrical statistical results of ≈110 devices on the polycrystalline diamond substrate, 44% of devices show normally‐off operation with a maximum current density of 400 mA mm −1, while 56% of devices demonstrate normally‐on operation with a maximum current density of 525 mA mm −1 . The normally‐off characteristics are more related to the higher amounts of nitrogen concentration than the grain boundaries. The stable boron‐doped source and drain provide a high concentration of holes, which facilitate transport in the surface p‐type channel induced by the H‐termination. The characteristics of the MOSFETs are inspiring for the fabrication of complementary inverter circuits on large diamond wafers. Abstract : This work presents an excellent metal‐oxide‐semiconductor field‐effect transistor (MOSFET) on a diamond substrate derived from a five‐inch (110) highly preferred polycrystalline diamond film. Forty‐four percentage of devices show normally‐off operation with a maximum current density of 400 mA mm −1, while 56% of devices demonstrate normally‐on operation with a maximum current density of 525 mA mm −1 .